A systematic review of soft skills interventions within curricula from school to university level - Orih, Dominic; Heyeres, Marion; Morgan, Rhian; Udah, Hyacinth; Tsey, Komla (Frontiers in Education, 2024)
BackgroundSoft skills are increasingly promoted in curricula, writ large in its scholarly interest over the last decade. Yet systematic literature reviews covering all educational stages are lacking. This review addresses this gap by examining soft skills interventions across all educational levels, evaluating their characteristics, design quality, and outcomes.MethodsA comprehensive search was conducted across ERIC, Scopus, Informit A+ Education, and Google Scholar databases from 2012 to 2022 to identify peer-reviewed studies on soft skills interventions within education curricula at all levels. Study characteristics were extracted, analysed and synthesised to inform conclusion. Quality assessment was performed using The Critical Appraisal Skills Programme (CASP) and the Effective Public Health Practice Project (EPHPP) evaluation tools. This study is registered at PROSPERO (CRD42022309833).ResultsThe search yielded 5,689 records, and after eligibility assessment, 38 studies were included. These studies employed various interventions that span three categories namely, workshop-based, creative-based, and project-based approaches, to enhance students’ soft skills. Reported outcomes encompassed improved soft skills, employability, career planning, social–emotional learning, academic performance, and reduced issues like violence, drug abuse, depression, and bullying. Quality appraisal using CASP and EPHPP tools identified three studies as “best practice” among the 38. The review highlights diverse interventions and positive impacts on students’ holistic development through soft skills programs.ConclusionThe analysis of 38 studies underscores the shortage of literature on soft skills in primary and secondary schools compared to universities, a lack of high-quality “best practice” resources for soft skills development, and a tendency for control group participants to miss vital soft skills training. While randomised controlled trials (RCTs), considered as gold standard, informed ‘best practice’ studies, RCTs may not fully capture the nuances of complex social interventions like soft skills programs. Therefore, there is need for alternative approaches, such as continuous quality improvement studies using mixed methods. Consequently, we recommended that future research consider these aspects to enhance the effectiveness of soft skills development in curricula.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022309833, identifier CRD42022309833.